Corporate Social Responsibility (CSR) Disclosures, Board Of Directors And Company Profitability: Audit Quality As Moderation - Wicaksono, Agung Prasetyo Nugroho; Wahyuningtias, Adhinni Lailiya; Amalia, Firda Ayu; Dewananda, Wiharta (Universitas Muhammadiyah Malang, 2023)
Purpose: This study aims to examine the effect of corporate social responsibility (CSR) and the board of directors on the company's profitability with audit quality as moderating variable. Methodology/approach: The population in this study are manufacturing compannies sub-sectors of food and beverage listed on the Indonesia Stock Exchange (IDX) in 2019 – 2021. The sampling method uses purposive sampling with a total sample were 56. The data analysis method used data panel analysis and moderated regression analysis. Findings: The result of this study shows that corporate social responsibility (CSR) has a significant effect on the company's profitability which was proxied by ROA, while the board of directors has no significant effect on the company's profitability which was proxied by ROA, and audit quality cannot affect the relationship between corporate social responsibility (CSR) and the company's profitability which was proxied by ROA, but audit quality can affect the relationship between the board of directors and the company's profitability which was proxied by ROA. Practical implications: This shows that in making a decision, audit quality is very important because high audit quality will strengthen decision-making carried out by the board of directors. With the high quality of the audit, the board of directors will be assisted in making decisions to obtain favorable results for the company and to increase the company's profitability Originality/value: The more CSR that is carried out by a company, the higher the ROA obtained, so the productivity of assets in obtaining net profit is getting better. The better a company is at obtaining net income, the greater the attractiveness of investors to the company because the rate of return will be greater.